The impact of the COVID-19 pandemic and the Russian invasion of Ukraine on Gold markets - Morina, Fisnik; Misiri, Valdrin; Dinaj, Saimir; Grima, Simon (Business, Management and Economics Engineering, 2024)
Purpose – The study examines global Gold market performance and correlations between COVID-19, the Russian invasion, inflation, investors’ fear, asymmetric shocks, and the VIX (volatility index) impact on volatility.Research Methodology – This research uses an econometric approach to analyse the impact of COVID-19 and the Russian invasion on Gold market performance – specifically the ARCH (Autoregressive Conditional Heteroskedasticity) – GARCH (Generalized Autoregressive Conditional Heteroskedasticity) Model and the Threshold-Asymmetric ARCH Model.Findings – The study reveals that the COVID-19 pandemic and the Russian invasion of Ukraine have significantly impacted Gold market dynamics. Inflation significantly impacts volatility, emphasising the need for monitoring inflation rates. Investor fear increases demand during uncertainty periods, while negative shocks have a higher asymmetric effect. The VIX positively affects Gold market volatility, suggesting a perceived safe-haven status during increased volatility.Research Limitations – Gaps in the data related to COVID-19 cases, geopolitical events, and Gold market performance could potentially introduce inaccuracies, biases or limitations to the analysis.Practical Implications – The study’s findings have practical implications for investors, analysts, and policymakers involved in the financial investment of Gold markets.Originality/Value – This study provides new insights into the relationships between inflation, investor fear, asymmetric shocks, and the impact of the VIX on Gold market dynamics during economic and geopolitical uncertainty.